Green synthesis of copper oxide nanoparticles using Cedrus deodara aqueous extract for antibacterial activity. (2021) - Ramzan, M.; Obodo, Raphael.M.; Mukhtar, S.; Ilyas, S.Z.; Aziz, Fahad; Thovhogi, N.
Graphical abstract: Highlights: Facile, nontoxic and low cost approach were used for fabrication of nanoparticles. Cedrus deodara extract was used as a safe and compatible reducing agent. Nanoparticles formed had spherical morphology with uniform symmetry. CuO nanoparticles showed efficient antibacterial activity. Abstract: The study of copper oxide nanoparticles green synthesis was carried out using facile, nontoxic, and low-cost approach using extract of Cedrus deodara as a safe and compatible reducing agent. Scanning electron microscope (SEM), X-ray diffraction (XRD), UV–visible spectroscopy (UV–Vis), Transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FTIR) machines were used to characterize the nanoparticles formed. The FTIR showed that different phytochemical present in cedrus extract are accountable for the synthesis of CuO (copper oxide) nanoparticles. The XRD result depicted that CuO nanoparticles were monoclinic in nature. The SEM and TEM analysis also confirmed that formed nanoparticles had spherical morphology with uniform symmetry. The CuO nanoparticles were tested to inhibit the growth human pathogenic strains with the help of disc diffusion method against E. coli and S. aureus. It is noted that the formed CuO nanoparticles showed efficient antibacterial activity especially against E. coli with maximum inhibition zone of 29 mm.